Engineering modelling of structural details of a bridge - Stefan Pradelok; Piotr Bętkowski; Adam Rudzik; Piotr Łaziński (Budownictwo i Architektura, 2013)
This paper presents a method of engineering modelling of structural details, which enables the analysis of local static and dynamic effects in a complex structure with the use of a personal computer. An analysed structural detail, modelled with the use of shell finite elements, is mounted to a spatial truss member system. Then, on the basis of prepared computational model, a static or dynamic analysis is carried out. The proposed model allows to detect the local effects in a theoretical. Conducted analyses confirmed the correct operation of such a computational model. Hence, the method of modelling presented in this paper allows to analyse the local effects on ordinary personal computer and more importantly, the results of such calculations are available within a relatively short period of time. The calculations are carried out by analysing the local effects in a steel node of the truss railway bridge.